(untitled) (Eurasian Journal of Philology Science and Education, 2015)
Scientific research is devoted studying of a problem of lexical various ideas of the concept "horse" in Kazakh cultures for a position semantic and cognitive of the approach. Analyzed semantic features of lexical various the ideas of the concept reflect cognitive model of consciousness of the Kazakh people. Scientific novelty of the study is that it was aimed at the prototypical model of cognitive-semantic space concept. Synonymous groups learned by continuous sampling of the works of Kazakh literature, will provide access to the content of the concept "horse" and describe it. During the phase of cognitive interpretation of the description of lexical units analyzed the lexical-semantic field of the concept "horse" in the Kazakh culture, using semantic-cognitive analysis is described in detail by field basis of concept, in which the core is allocated (cognitive-propositional structure, the basic information content) , co-nuclear parts zone concept, representing the lexical synonyms, interpretative field, which is the purpose of research and periphery (sensory image, associative-type representations), which suggests that the "horse" is a marker of Kazakh culture.